Language and Maratabat: A Potential Source of Ethnic Conflict (Asia Pacific Journal of Social and Behavioral Sciences, 2018)
In almost all societies, people find the speech of others an irresistible target of criticism. This study aimed to analyse how language can be a source of conflict between Maranaos and Bisaya-speaking residents in Iligan City and Cagayan de Oro City. Data were gathered using the qualitative method of research involving twenty respondents. The findings revealed that when Bisaya-speaking locales hear individuals speak Maranao language they become cautious and distrustful. The Maranaos shared the same reaction. Both groups tend to withdraw and avoid possible interaction for fear of being misunderstood and offensive. There were instances when the Maranaos, to avoid criticism and conflict, would try to speak fluently in Bisaya hiding the Maranao accent. Since interaction is inevitable between the two groups, this study documented words used that violated the maratabat of Maranaos. Maratabat is the Maranaos' deep sense of personal honor, dignity, self-esteem, and reputation. This is one aspect that makes them different from the other ethnic groups in Southern Philippines. This study concludes that language can be a source of conflict for the Maranaos especially when their maratabat which gives them a sense of pride and honor that is violated.
Keywords: Language, maratabat, ethnic conflict, interpretive phenomenological analysis